M23C6 carbides and Cr2N nitrides in aged duplex stainless steel: A SEM, TEM and FIB tomography investigation. (May 2016) - Maetz, J.-Y.; Douillard, T.; Cazottes, S.; Verdu, C.; Kléber, X.
Abstract : Highlights: The complex precipitation occurring in duplex stainless steel is investigated in 3D. The FIB tomography operating and image-processing methodology is precisely described. Cr2 N and M23 C6 precipitates are segmented in the volumes from image contrast analysis. The evolution of the precipitation during ageing is assessed: morphology, fraction, size, etc. Abstract: The precipitation evolution during ageing of a 2101 lean duplex stainless steel was investigated, revealing that the precipitate type and morphology depends on the nature of the grain boundary. Triangular M23 C6 carbides precipitate only at γ / δ interfaces and rod-like Cr2 N nitrides precipitate at both γ / δ and δ / δ interfaces. After 15 min of ageing, the M23 C6 size no longer evolves, whereas that of the Cr2 N continues to evolve. For Cr2 N, the morphology is maintained at γ / δ interfaces, whereas percolation occurs to form a continuous layer at δ / δ interfaces. By combining 2D and 3D characterisation at the nanoscale using transmission electron microscopy (TEM) and focused ion beam (FIB) tomography, a complete description of the precipitation evolution was obtained, including the composition, crystallographic structure, orientation relationship with the matrix phases, location, morphology, size and volume fraction.